(3GdCeO GdCbUis - (3CHh RjO YHO Gddg Hf YeQ Hf YjSi GdOHhS,J (B430 (3g` s ((3eOjfI HdN s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CcQefi HCN Rci eRGLg hCPci SQGMg , bO EHJcQ GdcdGe HfhQ Ybdg hCeJdc GdfYe HhbhQ aVdg hCOQc GdMde HJhajb QHg s
(3BNQgG (B:s
(3HMeO SjO Cgd GdSGYI hUGMH GdTaGYI hYdi Bdg GdWGgQjf hCUMGHg s
(3GdfSNI HgG MhGTs
(3HBNQg Cfg EfJgJ GdebGHdI hGdJUMjM SfI (B775(3g` HeOjfI HdNs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B168s
Keywords: (3GdJUha hGdBOGH GdTQYjIs